(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify: Identify extended thinking among female students in the Kindergarten Department To achieve the research objective, the researcher selected the research community from female students in the Kindergarten Department at Al-Mustansiriya University / College of Basic Education. An extended thinking scale of (40) items was prepared. After extracting the psychometric properties of validity and reliability, the final version of the scale was developed and applied to the basic sample (220) female students. After statistically processing the data, the researcher concluded the following: That the members of the research sample have a high level of extended thinking